Changes in carotid artery structure with smoking cessation. (December 2019) - Mitchell, Carol; Piper, Megan E; Smith, Stevens S; Korcarz, Claudia E; Fiore, Michael C; Baker, Timothy B; Stein, James H
Carotid artery grayscale ultrasound echogenicity and texture features predict cardiovascular disease events. We evaluated the longitudinal effects of smoking cessation on four grayscale ultrasound measures. This was a secondary analysis of data from 188 age, sex, and body mass index (BMI)-matched smokers (94 eventual abstainers [EA], 94 continued smokers [CS]) from a smoking cessation trial that had carotid ultrasound examinations at baseline and after 3 years. General linear models that included time, smoking group (EA or CS), and a time*smoking interaction term were used to examine the impact of smoking abstinence on carotid artery grayscale marker values at year 3. Participants were mean (SD) 50.3 (11.4) years old (57% female, 86% white). The baseline grayscale median value (GSM) was inversely correlated with age, BMI, insulin resistance, and smoking pack-years ( r = −0.20 to –0.30, p < 0.007 for all). There was a significant time*smoking status interaction for predicting GSM at year 3: GSM decreased significantly in the EA group compared to the CS group (–3.63 [13.00] vs CS 0.39 [12.06] units; p = 0.029). BMI increased more in the EA than the CS group (2.42 [3.00] vs CS 0.35 [2.57] kg/m 2 ; p < 0.001). After adjusting for changes in BMI, the time*smoking status interaction no longer was significant ( p = 0.138). From baseline to year 3, contrast increased similarly in both groups. Entropy and angular second moment did not change significantly in either group. Changes in carotid ultrasound echogenicity and grayscale texture features during a smoking cessation attempt are modest and mostly related to weight gain. Clinicaltrials.gov Identifier: NCT01553084